Dedikasi Karyawan dalam Menjalankan Standar Akreditasi Di RS X (Journal of Hospital Management, 2019)
Low implementation of Accreditation standards on post-accreditation hospitals which can caused the revocation of hospital accreditation status. The purpose of this study was to analyze the effect of supervision and motivation on post-accreditation employee commitment with employee satisfaction as an intervening variable. The research uses quantitative research methods with survei methods using questionnaires and method of analysis using Structural Equation Model (SEM), Amos version 23. The results showed the supervision variable had a positive effect on post-accreditation employee commitment but had a negative effect on job satisfaction. Employee motivation has a positive effect on job satisfaction, but it has a negative effect on post-accreditation employee commitment, while job satisfaction has a positive effect on postaccreditation employee commitment. Study findings that job satisfaction can not be an intermediate variable between supervision with post-accreditation employee commitment. While the effect of work motivation on post-accreditation employee commitment can be mediated by job satisfaction. To increase post-accreditation employee commitment can be done by increasing work motivation through job satisfaction by growing employee dedication and integrity.Keywords: supervision, work motivation, post-accreditation employee commitment, job satisfaction